Modulation of pulmonary immune functions by the Pseudomonas aeruginosa secondary metabolite pyocyanin - Lew, Shi Qian; Chong, Sook Yin; Lau, Gee W. (Frontiers in Immunology, 2025)
Pseudomonas aeruginosa is a prevalent opportunistic Gram-negative bacterial pathogen. One of its key virulence factors is pyocyanin, a redox-active phenazine secondary metabolite that plays a crucial role in the establishment and persistence of chronic infections. This review provides a synopsis of the mechanisms through which pyocyanin exacerbates pulmonary infections. Pyocyanin induces oxidative stress by generating reactive oxygen and nitrogen species which disrupt essential defense mechanisms in respiratory epithelium. Pyocyanin increases airway barrier permeability and facilitates bacterial invasion. Pyocyanin also impairs mucociliary clearance by damaging ciliary function, resulting in mucus accumulation and airway obstruction. Furthermore, it modulates immune responses by promoting the production of pro-inflammatory cytokines, accelerating neutrophil apoptosis, and inducing excessive neutrophil extracellular trap formation, which exacerbates lung tissue damage. Additionally, pyocyanin disrupts macrophage phagocytic function, hindering the clearance of apoptotic cells and perpetuating inflammation. It also triggers mucus hypersecretion by inactivating the transcription factor FOXA2 and enhancing the IL-4/IL-13-STAT6 and EGFR-AKT/ERK1/2 signaling pathways, leading to goblet cell metaplasia and increased mucin production. Insights into the role of pyocyanin in P. aeruginosa infections may reveal potential therapeutic strategies to alleviate the severity of infections in chronic respiratory diseases including cystic fibrosis (CF) and chronic obstructive pulmonary disease (COPD).